Wound healing properties of the protein kinase A inhibitor and the mechanisms of their development (Bangladesh Journal of Pharmacology, 2021)
The regenerative activity of the protein kinase A inhibitor was investigated using externally on the model of the flap skin wound. The pronounced wound healing effects of the protein kinase A inhibitor had been revealed. They are based on the activation of mesenchymal progenitor cells. The development of this phenomenon was associated with the direct influence of the protein kinase A inhibitor on mesenchymal progenitor cells. The most significant stimulation of their growth potential occurred in the context of the impact of growth factors in particular fibroblast growth factor secreted by the stromal cells. Moreover, in situ, there was an increase not only in proliferating activity but also in the intensity of the specialization processes of progenitors. Without cytokines stimulation, the change in the pattern of cellular cAMP-mediated signal does not affect the maturation rate of precursors.